2011
DOI: 10.1007/s12098-011-0456-3
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance in Overweight and Obese North Indian Adolescents

Abstract: The present analytic study was planned to study the impact of overweight and obesity on glucose tolerance in adolescents. Thirty overweight (BMI analogue  ≥  25-29.9 kg/m(2)) and 30 obese (BMI analogue  ≥ 30 kg/m(2)) adolescents were included as cases and 30 healthy age and sex matched adolescents comprised the control group. All the study participants were subjected to oral glucose tolerance test (OGTT) as a measure of glucose tolerance.Means of fasting blood glucose levels in normal, overweight and obese gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…We used the World Health Organization age-and gender-specific cut points 24 as they included Indian children as part of the study population. Family history of diabetes and acanthosis nigricans have been previously shown to be associated with diabetes, more commonly in girls, 19,[28][29][30]32 as also seen in this study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We used the World Health Organization age-and gender-specific cut points 24 as they included Indian children as part of the study population. Family history of diabetes and acanthosis nigricans have been previously shown to be associated with diabetes, more commonly in girls, 19,[28][29][30]32 as also seen in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies from India, 29 Canada, 11 and Europe 33 have reported a higher prevalence of dysglycemia among overweight and obese adolescents. However, it is difficult to compare prevalence rates of glucose intolerance across studies in the young because of the use of different cut points and absence of country-specific normative data to identify children and adolescents who have generalized or abdominal obesity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Being overweight raises the risk of a series of diseases including high blood pressure, dyslipidaemia, heart disease and stroke [3][4][5]. The most common diseases associated with high body weight are insulin resistance (IR) [6][7][8], and glucose intolerance [9][10][11], which are the main causes of impaired glucose tolerance (IGT) and high blood glucose in adults and adolescents [12][13][14]. Earlier onset high body weight is associ-ated with impaired glucose metabolism [15], which can cause pronounced deterioration of insulin sensitivity, even at lower levels of body weight in overweight adolescents [16,17].…”
Section: Introduction ▼mentioning
confidence: 99%
“…Childhood obesity can increase medical costs in countries that already face financial constraints [24]. There are additional barriers to care in poorer settings, including India, such as long distances to medical facilities, overcrowding, understaffed medical facilities, lack of availability of treatments, and unequal access between rural and urban areas and between socioeconomic strata [25]. Medical personnel are often not trained or equipped to detect chronic diseases until these reach advanced stages [24].…”
Section: Introductionmentioning
confidence: 99%